Nation Branding Practices from the Perspective of Critical Geopolitics: A Case Study of the Hainan Free Trade Port - Luo Zhiwei; Wang Min (Redai dili, 2022)
Currently, the world is undergoing profound changes, and the rise of counter-globalization and trade protectionism is impacting global economic governance. The development of globalization faces major challenges. In this context, China proposed building the Hainan Free Trade Port in 2018, which was understood as both a necessity for China to deepen reform and open up and as an effort to actively reshape the geopolitical and economic environment in global governance. Taking the Hainan Free Trade Port and its geopolitical meaning as the research object, this study employed discourse analysis and netnography to explore geopolitical practices based on nation branding, examine how actors such as the government, media, and domestic and foreign audiences participate in the (re)production of the geo-meaning of the Hainan Free Trade Port, and discuss its geopolitical operational mechanisms in depth. The findings indicated the following: (1) The Chinese government utilized media tools for knowledge representation and production, disseminated grand narratives for domestic and foreign audiences, and worked to build national identity, emphasizing China’s role as a builder under regional and global systems. The audiences were not exclusively passive recipients of media messages, but participated in processing and reproducing them. (2) For domestic audiences, the national narrative inspired some audiences’ national awareness and legitimized Hainan's free trade port. Meanwhile, top-down meaning-making generated contradictory results in specific contexts and even triggered critical, bottom-up debates. For foreign audiences, owing to the political and cultural differences between China and the West, media messages were processed secondarily as a source of geographical imagination, which in turn shaped audiences’ subjective perceptions of the international geopolitical landscape. (3) Finally, the media played an important role in the brand construction process as an information “bridge.” On the one hand, the media served as a tool for the top-down and inside-out transmission of national narratives, creating a favorable public opinion environment for Hainan Free Trade Port’s construction. On the other hand, the media served as a medium for bottom-up and outside-in feedback of audience emotions. Nevertheless, it should be emphasized that the delivery and feedback paths still need to be negotiated for a positive nation branding operation. The contribution of this research is reflected in two aspects: Through the theoretical introduction and case analysis of the geopolitical meaning of nation branding, it provides an initial exploration of related research in China; and, in the context of China’s participation in global governance, it provides a realistic reference for the steady progress of the Hainan Free Trade Port.